Sex differences in the association between smoking and abdominal aortic aneurysm. Issue 10 (11th June 2014) - Stackelberg, O; Björck, M; Larsson, S C; Orsini, N; Wolk, A
Abstract: Background: It is unclear whether recommendations about ultrasound screening programmes for abdominal aortic aneurysm (AAA) among men should be extended to include women who smoke. The aim was to examine sex-specific dose–response associations between AAA risk and smoking status, pack-years smoked and time since smoking cessation. Methods: Women in the Swedish Mammography Cohort and men in the Cohort of Swedish Men were followed up from 1998 to 2011. AAA was identified through linkage of the cohorts to the Swedish Inpatient Register and the Swedish National Register for Vascular Surgery (Swedvasc), and not through general ultrasound screening. Associations were estimated with Cox proportional hazards models. Results: The cohorts included 35 550 women and 42 596 men, aged 46–84 years. During follow-up, AAA was identified in 199 women and 958 men. The incidence of AAA per 100 000 person-years was 76 among men who never smoked and 136 among women who currently smoke. Regarding AAA risk, women were more sensitive to current smoking ( P interaction = 0·002). Compared with never smokers, the hazard ratio (HR) for AAA in current smokers with more than 20 pack-years was 10·97 (95 per cent confidence interval 7·41 to 16·26) among women and 6·55 (5·36 to 7·99) among men. Following smoking cessation, women had a more rapid decline in excess risk ( P interaction < 0·001). The risk was halved after 11 years (HR 0·51, 0·32 to 0·81) among women and after 23 years (HR 0·50, 0·42 to 0·60) among men. Conclusion: There were sex differences in the associations between smoking status and AAA risk. These data support further investigation of targeted AAA screening among women who smoke. Abstract : Female smokers at greater risk